The utopia reader - Claeys, Gregory; Sargent, Lyman Tower, 1940- (New York University Press, 2017)
"The Utopia Reader compiles primary texts from a variety of authors and movements across history that have explored how to envision different ways of life, and why we do so. The volume includes texts ranging from classical Greek literature, the Old Testament, and Plato's Republic, to Sir Thomas More's Utopia, to George Orwell's Nineteen Eighty-Four and beyond. By balancing well-known and obscure examples, this volume provides a comprehensive and definitive collection of the various ways Utopias have been conceived throughout history and how Utopian ideals have served as criticisms of existing sociocultural conditions. This second edition includes many historically well-known works, little-known-but-influential texts, and contemporary writings, providing more expansive coverage of the varieties of approaches and responses to the concept of utopia in the past, present, and even the future. In this edition are more classic feminist writings and work by authors of color, as well as recent new trends such as ecological ideals of Utopia. Furthermore, Claeys and Sargent highlight popular twenty-first century narrative explorations of Utopias through the genres of young adult dystopias, survivalist dystopias, and non-print utopias. Covering a range of original theories of utopianism and revealing the nuances and concerns of writers across history as they attempt to envision different, ideal societies, The Utopia Reader remains an essential resource for students and scholars alike"--Page 4 of cover.